Performative Storytelling Design. Intertwining Art, Storytelling Design, and Neurodesign for Empathetic Connections in Workplaces - Eleonora D’Ascenzi (Pad)
The lack of empathy in the workplace leads to conflicts, reduced cohesion, and declines in productivity and job satisfaction (Danna & Griffin, 1999). Building on this premise, this contribution examines the strategic role of performative storytelling design as an innovative approach that combines storytelling design, immersive technologies, and performative art to foster empathic connections by encouraging perspective-taking, strengthening team cohesion, and promoting shared corporate values (Gorman, 2019; Green & Brock, 2000). To elucidate this aspect, the paper includes best practices that can foster mutual understanding, collaboration, and team building through value sharing. To test the effectiveness of this approach and provide scientific evidence, the paper underscores the value of neurodesign in quantitatively assessing the impact of immersive experiences on employee well-being, offering concrete data on physiological and psychological responses (Ulrich, 1984). In conclusion, the integration of performative storytelling design and its validation through neurodesign techniques emerges as a promising strategy for addressing workplace well-being challenges and optimizing corporate dynamics, particularly when implemented within short time frames and repeated over time. Looking ahead, future research should prioritize the hybridization of disciplines to boost productivity and team cohesion, while exploring the co-design of such experiences in partnership with health specialists and human resources managers.